APLIKASI ZERO WASTE MELALUI PEMBUATAN MINYAK ATSIRI DARI LIMBAH KULIT JERUK PERAS - Rangkuti, Khairunnisa; Ardilla, Desi; Ginting, Litna Nurjannah (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Nowadays, the number of orange juice business increases in Medan city. This business produces a byproduct that is discarded and not utilized by the seller. On the other hand,Â many people living in poverty and less empower because they don't have the skills to generate additional income. This program wants to use zero-waste concepts to empowering a community. Zero Waste is one of the solutions to the problem of handling Waste as well as the empowerment of people. Partner of this program is people of Program family Harapan (PKH) incorporated in Kelompok Usaha Bersama (KUBE) Rezeki Jermal located in the village of Denai, Medan. Socialization and training is the method used in this program. Derivative products of essential oil are repellent lotion and aromatherapy candles. The final result of this program are partner know the implication of zero Waste and have the skill to manage the Waste.